(untitled) (Jurnal Manajemen Bisnis, 2026)
This study is a correlational study with a population of 35 respondents. Data were collected through questionnaires and analyzed using product moment correlation techniques. The results showed that Marketing Strategy (X1) had a positive and significant effect on Gen-Z Photography Service Revenue (Y), indicated by the calculated t value > t table (0.730 > 1.689) and a significance value of 0.000 < 0.05. The Digital Service variable (X2) also had a significant positive effect, with the calculated t value > t table (8.972 > 1.689) and a significance value of 0.000 < 0.05. Furthermore, Sharia Business Ethics (X3) is proven to have a significant positive effect on income, as indicated by the calculated t value > t table (17,730 > 1,689) and a significance value of 0.000 < 0.05. Simultaneously, the three variables—Marketing Strategy, Digital Services, and Sharia Business Ethics—have a significant influence on the Income of Gen-Z Photography Services. This is evidenced by the calculated F value > F table (184.253 > 4.121) and a significance value of 0.000 < 0.05. This finding confirms that improving the quality of marketing strategies, digital services, and the implementation of Sharia business ethics can jointly increase the income of Generation Z photography service providers.